Relações de gênero, interseccionalidades e formação docente - Vasconcelos, Maria Nazareth Moreira (2018)
This research was carried out with the objective of critically analyzing the possible consequences of a proposal of teacher training in the discourses related to gender relations and intersectionalities. The realization of this study is justified by the perception of the difficulty of society, and consequently of the school, in dealing with the diversities, especially those that originate in the different identities of gender and sexual orientations. Gender relations are socially constructed and therefore permeated by power relations, causing differences to generate inequalities and result in violence against women and against LGBTI people, who historically have their rights denied. In this context, black, poor and subalternized girls, women and LGBTI people suffer from male chauvinist, but also from other types of oppression, which makes it necessary to use gender as a category of analysis from the perspective of intersectionality, to understand how diverse types of oppression operate simultaneously on people's lives. The school carries within itself the possibility of combating prejudice and the inequalities produced historically, but for this it is imperative that educators be trained to look strangely at instituted stereotypes. Based on this, the formative meetings were held and were constituted as object of analysis of this research, with professionals from two municipal schools of Elementary School of São Paulo. The training proposal was elaborated based on the ideas of authors who think about teacher education in a critical and reflexive perspective, as well as on the assumptions of the Social-Historical-Cultural Activity Theory, the fruit of the works of Vygotsky (1934/2007), Leontiev (1978/2004) and Engeström (1987). Gender and intersectionality studies have also been taken as the basis for how gender inequalities have been / are produced. The methodology used was that of the Collaborative Critical Research, which attributes to language the mediating and constitutive role of human relations and has the premise of dialogue and commitment to the transformation of reality. The data were produced through three procedures: questionnaires delivered to the participants; collection of census data in electronic portals and institutional documents of schools and transcription of the recording of training meetings. The analysis of the data was based on the actions of describing, informing, confronting and reconstructing, pertinent to the reflective process. The main results showed that it is possible for a formation to cause changes in the discourses of educators about gender relations and intersectionalities, making them understand the role of the school in the fight against prejudice, racism and LGBTIphobia. It was possible to realize, however, that it is necessary to offer a training that also allows the experience of concrete activities and not only the discussion of ideas, so that people feel more mobilized to carry out activities with the theme of the training in the classroom, thus becoming real agents of change